Features of identification of grain thermal processing - Kalinichenko, R. (Energy and Automation, 2026)
The article considers the processes of heat and mass transfer during convective drying of grain material. The purpose of the work is to develop and identify a mathematical model of grain heating and drying kinetics, taking into account variable thermophysical properties of the material. As a basic model, a system of differential equations proposed by O.V. Lykov is used for a thin grain layer, considering the non-stationary nature of the process and the dependence of moisture diffusivity coefficients on the temperature and moisture content of the grain kernel. A simplified analytical relationship for the drying coefficient is proposed, which makes it possible to reduce the computational complexity of the analytical solution of the model without loss of accuracy. Model parameters were identified based on experimental data using the inverse problem method and the analytical solution of the proposed mathematical model. Empirical dependences of the model coefficients on the initial grain moisture content and the main operating parameters of the drying process were obtained. The results of numerical simulation using the model with identified variable coefficients show good agreement with experimental data, which is confirmed by a high value of the multiple correlation coefficient (R = 0.96–0.99). The proposed mathematical model with variable identified coefficients can be used to predict grain drying kinetics when determining rational operating modes of grain dryers and developing intelligent control systems aimed at increasing the energy efficiency of the process while maintaining grain quality. Recieved 2025-12-01 Recieved 2026-02-01 Accepted 2026-02-11